Estudo por RMN no estado sólido sobre a ocorrência de fósforo em materiais carbonosos obtidos por tratamentos térmicos na presença de ácido fosfórico. - Honorato, Hercílio de Angeli (2012)
This work is devoted to a study of the occurrence of phosphorus in carbon materials obtained by heat treatments of organic precursors impregnated with H3PO4. Solid state nuclear magnetic resonance (NMR) was used as the primary characterization technique. Three different precursors were used for production of the biochars: peat, the endocarp of babassu coconut and the testa of an ironwood oil seed (Mesua ferrea). In this work, peat samples were subjected to heat treatments in the presence of H3PO4, leading to the incorporation of phosphorus into the structure of the produced biochars and in some cases to an increase in porosity. The resulting material was then analyzed by 31P and 13C NMR under high magnetic field, among other characterization methods, in order to investigate the natureof the phosphorus-containing species in the structure of the biochars. The materials derived from the other precursors were prepared in previous studies and were analyzed here with the same techniques used for the peat-derived samples. The results showed that phosphorus was incorporated into the carbon matrices as phosphate groups, in most cases bonded to aliphatic groups. The formation of polyphosphate chains was observed at relatively low heat treatment temperatures (~350°C), but these groups were decomposed with the increase in the heat treatment temperature. By X-ray diffraction (XRD), it was possible to observe a beneficial effect of the phosphorus presence for the process of structural organization of graphene planes within the turbostratic microcrystallites. 31P NMR and XRD results also revealed the formation of the compound SiP2O7in the case of the babassu-derived samples, due to the significant silicon content in the endocarp of babassu coconut. This compound was detected in different crystal phases, depending on the preparation conditions. Finally, it was observed that the surface area of the products, as well as the nature of the phosphorus-containing groups within the carbon matrix, is dependent upon the type of precursor and on the chemical andthermal treatments used for the preparation of the analyzed materials